Season Metaphors In English And Vietnamese Songs: A Cognitive Study - Th.S Sỹ Thị Thơm (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
In the light of the conceptual metaphor theory (CMT), initiated by Lakoff and Johnson (1980), this study aims at investigating the conceptualization of season in English and Vietnamese songs. Accordingly, the study is intended to identify the metaphors of SEASON in both languages. It is the viewpoint of metaphors in pre-cognitive and cognitive periods that serves to build the theoretical framework for this study. Methodologically, the data are collected from English and Vietnamese song lyrics written from the 20th century to present. Comparative method was mainly employed in combination with descriptive method. Especially, the thesis employed the procedure of the identifying of conceptual metaphors proposed by Steen (2007) and Pragglejaz Group (2007). Thus, the two methods of metaphor analysis, namely Metaphor Pattern Analysis (MPA, Stefanowitsch 2006) and the version of the Metaphor Identification Procedure developed at Vrije Universiteit (MIPVU, Steen et al. 2011) were used to characterize how conceptual metaphor of season is expressed. This comparative analysis of the conceptual metaphors of season in English and Vietnamese revealed that the two languages show a very similar conceptualization of season-related expressions. In detail, the research findings disclose 58 metaphors in total. Regarding SEASON as the target domain of a metaphorical mapping, 40 metaphors are found in both English and Vietnamese. The songs in two languages share 28 metaphors, and there are 12 metaphors which are unique to one language but not the other. In terms of SEASON considered as the source domain, 10 shared metaphors of SEASON are found in the both corpora. Simultaneously, 6 metaphors are existent in Vietnamese, but not present in English. In contrast, there are 2 cases found in English data only. It can be concluded that there are both similarities and differences in metaphorizing the entity SEASON in between English and Vietnamese based on the physical and socio-cultural environment. Particularly, the two languages share the great number of the season metaphors as regards season treated as the target domain with the basement of iv metaphor interpreting via mainly physical environment while the differences of season metaphors in these languages are mainly in conceptualizing season as the source domain based on the differences related to socio-cultural environment. The dissertation, as briefly described above, is hoped to make significant contribution to the teaching, learning and English-Vietnamese translating practice.